2020
DOI: 10.3390/nu12051501
|View full text |Cite
|
Sign up to set email alerts
|

Two Faces of Vitamin C—Antioxidative and Pro-Oxidative Agent

Abstract: Vitamin C has been known for decades. It is common in everyday use as an element of the diet, supplementation, and a preservative. For years, research has been conducted to precisely determine the mechanism of action of ascorbate in the cell. Available results indicate its multi-directional cellular effects. Vitamin C, which belongs to antioxidants scavenging free radicals, also has a ‘second face’—as a pro-oxidative factor. However, whether is the latter nature a defect harmful to the cell, or whether a virtu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
190
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 223 publications
(194 citation statements)
references
References 110 publications
4
190
0
Order By: Relevance
“…In line with extensive literature arguing for beneficial effects of vitamin C treatment in cancer prevention [ 46 ], Gacitúa et al recently underscored the sizeable relevance of plasma vitamin C as a novel potentially modifiable risk factor for premature mortality post-kidney transplantation by describing an independent inverse association with risk of death, particularly death due to malignancy [ 47 ], potentially by counteracting toxic effects of maintenance immunosuppression therapy, specifically calcineurin inhibitors, which are the most accepted risk factor for de novo malignancy post-kidney transplantation [ 48 ]. Interestingly, in the current study, we observed signs of an inverse relationship between use of calcineurin inhibitors and plasma vitamin C, which may be in line with the data of the two randomized clinical trials of vitamin C performed in KTR, reporting an inverse association between vitamin C supplementation and cyclosporine A trough levels [ 49 , 50 ].…”
Section: Discussionmentioning
confidence: 56%
“…In line with extensive literature arguing for beneficial effects of vitamin C treatment in cancer prevention [ 46 ], Gacitúa et al recently underscored the sizeable relevance of plasma vitamin C as a novel potentially modifiable risk factor for premature mortality post-kidney transplantation by describing an independent inverse association with risk of death, particularly death due to malignancy [ 47 ], potentially by counteracting toxic effects of maintenance immunosuppression therapy, specifically calcineurin inhibitors, which are the most accepted risk factor for de novo malignancy post-kidney transplantation [ 48 ]. Interestingly, in the current study, we observed signs of an inverse relationship between use of calcineurin inhibitors and plasma vitamin C, which may be in line with the data of the two randomized clinical trials of vitamin C performed in KTR, reporting an inverse association between vitamin C supplementation and cyclosporine A trough levels [ 49 , 50 ].…”
Section: Discussionmentioning
confidence: 56%
“…Probably one of the most classical and powerful antioxidants in plants is vitamin C (vitC) or L-ascorbic acid ( Figure 4 a). The molecule is widely recognized as one of the central antioxidants in living cells, and helps to detoxify a broader range of ROS such as hydrogen peroxide, hydroxy radicals, superoxide anion radicals, singlet oxygen, and peroxy radicals [ 105 ]. In humans it is also needed for a variety of biosynthetic steps such as collagen and carnitine production, amidation of certain peptide hormones and tyrosine metabolism [ 106 , 107 , 108 , 109 , 110 ].…”
Section: Vitamin-based Antioxidantsmentioning
confidence: 99%
“… 3 Paradoxically, a pro-oxidant role for vitC has also been reported at high doses or in presence of transition metals. 104 High doses of vitC induce cytotoxicity in cancer cells, 105 and it was thus evaluated as a therapeutic agent in CRC patients. However, the results are inconsistent 106 ( Table 2 ).…”
Section: Testing Exogenous Antioxidants In Cacmentioning
confidence: 99%